Infliximab Biosimilars in the Age of Personalized Medicine. Issue 10 (October 2018) - Kang, Jukyung; Pisupati, Karthik; Benet, Alexander; Ruotolo, Brandon T.; Schwendeman, Steven P.; Schwendeman, Anna
Abstract : Structural and functional differences between REMICADE and its two FDA-approved biosimilars appear to have clinical implications. We suggest a personalized biosimilar substitution approach based on prescribed indication, biosimilar afucosylation level, and a patient's FCGR3A polymorphism. We also advocate for establishing glycosylation variation limits for biosimilar approvals.